Role of diffusion-weighted imaging, apparent diffusion coefficient and correlation with hepatobiliary phase findings in the differentiation of hepatocellular carcinoma from dysplastic nodules in cirrhotic liver. - Inchingolo, Riccardo; De Gaetano, Anna; Curione, Davide; Ciresa, Marzia; Miele, Luca; Pompili, Maurizio; Vecchio, Fabio; Giuliante, Felice; Bonomo, Lorenzo (European Radiology, 2015)
Objectives: To investigate the utility of diffusion-weighted imaging (DWI), apparent diffusion coefficient (ADC) and the correlation with hepatobiliary phase (delayed phase imaging, DPI) findings in the differentiation of cirrhotic hepatocellular nodules. Methods: Forty-three patients with 53 pathology-proven nodules (29 hepatocellular carcinomas (HCCs), 13 high-grade (HGDNs) and 11 low-grade dysplastic nodules (LGDNs); mean size 2.17 cm, range 1-4 cm), who underwent liver MRI with DWI and DPI sequences, were retrospectively reviewed. Lesions were classified as hypointense, isointense, or hyperintense relative to the adjacent liver parenchyma. ADC of each nodule, of the surrounding parenchyma, and lesion-to-liver ratio were calculated. Results: Hyperintensity versus iso/hypointensity on DWI, hypointensity versus iso/hyperintensity on DPI, and the mean lesion-to-liver ratio showed a statistically significant difference both between HCCs versus DNs and between 'HCCs + HGDNs' versus LGDNs ( p < 0.05); sensitivity, specificity, and accuracy for the diagnosis of 'HCCs + HGDNs' were 96.8 %, 100 %, 97.4 % respectively when combining hyperintensity on DWI and hypointensity on DPI, and 90.9 %, 81.0 %, 83.6 % respectively when lesion-to-liver ratio was <0.95. Conclusions: Hyperintensity on DWI, especially in association with hypointensity on DPI, and low lesion-to-liver ratios should raise the suspicion of HCC, or at least of HGDN, thus helping the characterization of atypically enhancing lesions. Key points: • Usefulness of DWI and ADC is shown in differential diagnosis of cirrhotic nodules. • Correlation of DWI with DPI improves differential diagnosis of cirrhotic nodules. • Characterization of atypically enhancing lesions becomes more confident.